PENGARUH INTELLECTUAL CAPITAL TERHADAP BUSINESS PERFORMANCE DENGAN PENDEKATAN BALANCED SCORECARD PADA PERUSAHAAN MANUFAKTUR BERSKALA BESAR DI SURABAYA - Nurul Kompyurini (Universitas Trunojoyo Madura, 2010)
The purpose of this empirical research is to examine influenced the three elements of intellectual capital that are human capital, structural capital, and customer capital with business performance.Data used for this research was collected from human resources development, financial, marketing, and R D manager. Data collected by contact person. 37 questionnaires were sent to managers from big scale manufactur enterprises in Surabaya. Analysis was conducted using Linear Multiple Regression with SPSS 11.0 softwares.The main conclusions from this research are that : human capital, structural capital, and customer capital simultaneously have positive and significant influence with business performance human capital has positive and significant influence with business performance, structural capital has positive and significant influence with business performance, and customer capital has positive and significant influence with business performance.